Multifunctional Polypyrrole-Based Textile Sensors for Integration into Personal Protection Equipment - Carolin Gleissner; Paul Mayer; Thomas Bechtold; Tung Pham (Sensors, 2024)
Integrated safety sensors for personal protection equipment increasingly attract research activities as there is a high need for workers in delicate situations to be physically monitored in order to avoid accidents. In this work, we present a simple approach to generate thin, homogeneous polypyrrole (PPy) layers on flexible textile polyamide fabrics. PPy layers of 0.5–1 µm were deposited on the fabric, which thus kept its flexibility. The conductive layers are multifunctional and can act as temperature and gas sensors for the detection of corrosive gases such as HCl and NH3. Using three examples of life-threatening environments, we were able to monitor temperature, atmospheric NH3 and HCl within critical ranges, i.e., 100 to 400 ppm for ammonia and 20 to 100 ppm for HCl. In the presence of HCl, a decrease in resistance was observed, while gaseous NH3 led to an increase in resistance. The sensor signal thus allows for distinguishing between these two gases and indicating critical concentrations. The simple and cheap manufacturing of such PPy sensors is of substantial interest for the future design of multifunction functional sensors in protective clothing.